Tribological Aspects of Cast Iron Investigated Via Fracture Toughness - C. Fragassa (Tribology in Industry, 2016)
Linear-elastic plane-strain fracture toughness of metallic materials is a method which covers the determination of the strain fracture toughness (KIC) of metallic materials by increasing-force test of fatigue precracked specimens. This method has been applied for investigating the fracture behaviour of cast iron. Two groups of cast alloys, Compacted Graphite Iron (CGI) and Spheroidal Graphite Iron (SGI) have been investigated. While SGI benefits of a wide scientific literature, CGI is a relatively unknown material despite of its large potentialities in industrial applications.